Pengaruh Model Kooperatif Tipe Think Pair Share Berbantuan Aplikasi Google Classroom terhadap Hasil Belajar Fisika Siswa - Alwia; Syamsu (Universitas Tadulako, 2021)
This study aimed to determine whether there is an effect of the Think, Pair & Share cooperative learning model assisted by the Google Classroom application on the physics learning outcomes. The type of research used was a quasi-experimental. The population of this study was all class X SMA Labschool UNTAD Palu with purposive sampling technique. The samples of this study were class X MIA 1 (n=24 as the experimental class) and class X MIA 2 (n=22 as the control class). The instrument of this research was a test of physics learning outcomes in the form of multiple choice which has been validated through item validation. The test of physics learning outcomes obtained showed that the average score of the experimental class was 17.92 and the control class was 12.05. Hypothesis testing or t-test (two parties) obtained tcount = 19.46 and ttable = 1.68 at the significant level = 0.05. It means that tcount is outside the area of ​​H0 acceptance, thus H0 is rejected and H1 is accepted. In other words, there is an influence of the Think, Pair & Share cooperative learning model assisted by the Google Classroom application on the learning outcomes of class X SMA Labschool UNTAD Palu students.